Characterization of regulatory elements in OsRGLP2 gene promoter from different rice accessions through sequencing and in silico evaluation. (April 2018) - Mahmood, Tariq; Tahir, Tamkeen; Munir, Faiza; Shinwari, Zabta Khan
Graphical abstract: Highlights: The Os RGLP2 promoter region includes vital regulatory factors that are TATA and CAAT Box, ARR1, GATA, AGAAA, CAAT and Dof factors. These regulatory factors function in growth, differentiation, seed storage protein, light responses and plant defense. HFH-1 transcription factor interacts with the A-T rich regulatory elements in high affinity with lysine and arginine. Among the studied DNA-protein interactions, HFH-1-ATAACAAAAGT with lowest cluster size showed high degree of stability. α-Helices of HFH-1 mostly form bonds with major groove of DNA and β-strands mostly interacts with minor groove. Abstract: Germins and germin-like proteins from cupin superfamily contribute resistance to heat denaturation, chemical degradation and against plant pathogens, further functions in plant growth and development. In this study, from three different Oryza sativa accessions KS-282 and Pak 7178 and Pak 7865, Os RGLP2 gene promoter region was amplified, sequenced and analyzed. Sequencing data was evaluated via different computational tools. The regulatory elements were predicted by Consite tool and mapping was done. Many transcription factors binding sites were discovered in Os RGLP2 gene promoter; among these factors, HFH-1 having a significant role in germination was picked for further investigation. To study the interaction between HFH-1 and corresponding regulatory factors, HADDOCK Webserver was used. Graphical models for the interactions of HFH-1 and related regulatory elements were studied by graphic molecular system PyMOL. Mapping of cis- acting regulatory elements in Os RGLP2 gene promoter from three rice accessions showed differences in their position and copy number. Important regulatory elements found in Os RGLP2 promoter region were TATA, CAAT Box, ARR1, GATA, AGAAA, CAAT and DNA-binding One Zinc Finger (Dof) factors, few of them contribute to the regulation of plant defensive system, light responses, developmental and growth activities. Furthermore, during DNA interaction studies, it was found that HFH-1 transcription factor participates in hydrogen bonds formation with thymine and adenine bases.